Letter (copy) : Speech of Caballero - Citrine, Walter, 1887-1983
011-0027-001 WMC/WJB/AC/121 International 28th October, 1937 Madame Lily Krier-Becker, Chambre de Travail, LUXEMBÜRG. la, rue Beaumont. Dear Madame Krier-Becker, SPEECH OF CABALLERO. You were good enough to send to me a statement in French of the recent crisis in the Spanish U.G.T. in accordance with the declarations made by Comrade Caballero. I am much indebted to you for your kindness in sending me this report. If it is not troubling you too much, could you indicate the source of the information you give? Was it drawn from any newspaper, or did you obtain a shorthand report of Comrade Caballero's speech and take the information from that? This is rather what your message would seem to imply. I would not, of course, bother you myself, but some of my colleagues have put the question to me, and I should like to be able to answer, if possible. Thanking you in advance, and with kind regards, Yours faithfully, General Secretary. 292/946/11/27